2019
DOI: 10.1002/jcp.29387
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of MMP‐9 by HuR contributes to IL‐1β‐induced pterygium fibroblast migration and invasion

Abstract: Inflammation is considered to be critical in the pterygium progression and recurrence. However, the underlying molecular mechanism is not well understood. Herein, we investigated the potential role of RNA binding protein human antigen R (HuR) responsible for the impact of inflammation on pterygium development. The expression of HuR and matrix metallopeptidase‐9 (MMP‐9) in pterygium and normal conjunctiva was detected with immunohistochemistry and quantitative reverse transcription polymerase chain reaction (qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…In particular, MMP9, a member of MMP superfamily, has been confirmed to be deeply involved in the metastasis of liver cancer ( 16 18 ). Moreover, it has also been reported that RNA binding protein HuR could increase the expression of MMP9 via maintaining MMP9 mRNA stability ( 19 ), indicating a potential underlying association between RBPs and MMP9 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP9, a member of MMP superfamily, has been confirmed to be deeply involved in the metastasis of liver cancer ( 16 18 ). Moreover, it has also been reported that RNA binding protein HuR could increase the expression of MMP9 via maintaining MMP9 mRNA stability ( 19 ), indicating a potential underlying association between RBPs and MMP9 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover known as the class embryonic death abnormal visual, widely expressed in mammalian cells [ 3 ]. It has been found to affect mRNA translation [ 21 ], cell responses [ 22 ], and inflammatory tumor formation [ 6 ]. In recent years, more studies have found that HuR is associated with the occurrence and prognosis of different carcinoma, glioma [ 8 ], breast cancer [ 9 ], lung cancer [ 10 ], and colorectal cancer [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Xue et al reported that microRNA-133b (miR-133b) plays a suppressor role in several human cancers, as well as glioma [8], colorectal cancer [11]. MicroRNAs (miR-NAs) are small noncoding RNAs that bind to mRNAs and regulate gene expression at the posttranscriptional level [5][6][7]. There are a lot of evidence revealing that miRNAs' expression is maladjusted in many cancers, but more studies are needed to confirm how it affects tumorigenesis and metastasis.…”
Section: Disease Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, molecular mechanisms of MMP9 upregulation in HCC are largely unknown. It has reported that the expression of MMP9 could be upregulated by RNA binding protein HuR via stabilizing of MMP9 mRNA 23 , indicating that RBPs may involve in MMP9 regulation.…”
Section: Introductionmentioning
confidence: 99%